2017
DOI: 10.1080/19475683.2017.1304449
|View full text |Cite
|
Sign up to set email alerts
|

Satellite data planning for flood mapping activities based on high rainfall events generated using TRMM, GEFS and disaster news

Abstract: Microwave satellite data enable the mapping of flooding over large areas, irrespective of cloud and weather conditions. Efficient planning of microwave data for acquiring satellite images over flood-affected areas for flood assessment and mapping needs prior information about the probable flood areas. Analysis of rainfall trend over a particular region over a time can help in predicting the flood-like situation and probable flood areas. Forecasts from weather forecasts models provide a fair idea about high rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another factor which considerable mentioned in the literature and plays a pivotal role in flood susceptibility mapping is rainfall (Breinl et al, 2021;Das and Scaringi, 2021;Sharma et al, 2017). There is a significant association between the rainfall and flooding throughout the area under study.…”
Section: Rainfallmentioning
confidence: 99%
“…Another factor which considerable mentioned in the literature and plays a pivotal role in flood susceptibility mapping is rainfall (Breinl et al, 2021;Das and Scaringi, 2021;Sharma et al, 2017). There is a significant association between the rainfall and flooding throughout the area under study.…”
Section: Rainfallmentioning
confidence: 99%
“…Afew studies have explored using rainfall data from satellite data such as Tropical Rainfall Measurement Mission (TRMM) to overcome this gap (Indu and Nagesh Kumar, 2014;Mondal et al, 2018). Attempts have also been made to integrate the satellite data with forecasting systems to improve the performance of the models in predicting floods (Sharma et al, 2017;Mitra et al, 2013). However, there are high uncertainties associated with precipitation, and still gaps exist in precisely quantifying the uncertainties in literature.…”
Section: Uncertainty Quantificationmentioning
confidence: 99%
“…Arabindoo (2016) discussed the argument among environmentalists and the administration where the former targeted the haphazard urbanization as a strong reason for the floods in the city and the later considered it as an unprecedented climate anomaly in the history of the city. Sharma et al (2017) showed the potential of global rainfall products (Tropical Rainfall Measuring Mission (TRMM)) and global forecast precipitation products (Global Ensemble Forecast System (GEFS) in successful flood mapping of the region. Methods such as map and site analysis, focus group interview and questionnaire survey were employed by Muneerudeen (2017) to compose urban and landscape design strategies for flood resilience.…”
Section: Chennai Citymentioning
confidence: 99%